Ownership of Knowledge Relative Surplus Value and Renewal of the State - Zavaleta Huaccha, William (2006)
Once the consensus has been established in the academic community on the importance of knowledge in the production and creation of value in the economy, it is necessary to explore the relationship between ownership of knowledge and accumulation or distribution of wealth.